The efficacy of specific immunocorrection drugs against ovine oestrosis - V. A. Marchenko (Российский паразитологический журнал, 2021)
The purpose of the research is to characterize the effect of specific immunocorrection drugs on the survival rate of the sheep botfly larvae and the immune response of the host organism. Materials and methods. Three variants of laboratory samples of specific immunocorrection drugs against sheep oestrosis have been developed based on water-soluble proteins of Oestrus ovis L. and Lucilia serricata Mg. larvae. The studies were carried out on 12 test and 3 control groups of lambs born in the current year artificially infected with 80 larvae of the sheep botfly. Fourteen days before infection, the test lambs were immunized with the prepared drugs. The drugs were injected subcutaneously in various doses (2–6 ml) and repeatedly (1–3) or by a single intranasal irrigation at a dose of 10 ml per animal. The efficacy was evaluated for the early (July – September) and summer-spring (August – April) periods of parasitism. In the test and control animals, we determined specific antibodies (JgG), stable E-rosette-forming cells (sE-RFC) and antigen-reactive (AR-RFC) T-lymphocytes. Results and discussion. The tested specific immunocorrection drugs based on somatic proteins of the sheep botfly and the sheep green bottle larvae have a pronounced protective effect against ovine oestrosis. In experiments, being affected by various drug variants, 44.6–99.1% of the sheep botfly larvae died in the early period of parasitism, and 22.6–88.1% of the sheep botfly larvae died in the summer-spring period. Subcutaneously injected drugs stimulate the produced specific antibodies and activate the effector function of the T-cell immune system to a greater extent than intranasal irrigation.